Upaya Guru Pendidikan Agama Islam Dalam Membina Akhlak Siswa (Studi Kasus di SMA Muhammadiyah 1 Sukoharjo Tahun Pelajaran 2015/2016) - Hajri, Muhammad Fatkhul; , Drs. Zaenal Abidin, M.Pd; , Drs. Arief Wibowo, M.Ag (2017)
One carried out in order to anticipate and develop the students' potential learners to prevent deviant behavior in society. Is to instill religious values and societal norms. They need to be guided on the positive things, this is where the personality of a good teacher will be instrumental in developing the character of students. The problem in this research is how the efforts of Islamic education teachers in developing student character in SMAMuhammadiyah 1 Sukoharjo Year 2015/2016? Therefore the purpose of this study was to describe the efforts of teachers of Islamic education in fostering morals students at SMA Muhammadiyah 1 Sukoharjo in the academic year 2015/2016. The research was conducted in SMA Muhammadiyah I Sukoharjo. with a class XI student study sample. This research is a field research (field research) with a qualitative approach. Average data collection was conducted through interviews, observation, and documentation and data analysis through qualitative analysis methods that are descriptive. Research, the first implementation of coaching done by habituation discipline morals, manners, social care, religious rituals; The second problem that arises is there are still not following the discipline as extracurricular activities. As for manners, there are still many students who are reluctant to say hello and shake hands with the teacher. On social care, there are students that love to spend money for the sake of infaq; Third Giving punishment to those who are not disciplined. Giving good models for the governance kramanya poor, and those who have berinfaq, held motivation. The recommendation is to discipline for teachers and students with a rigorous discipline